Avaliação de riscos em salões de beleza - Borges, Talita (2016)
About seven thousand of beauty saloons are opened every month in Brazil. With around 4.4 million of professionals, the beauty industry is increasing expressively all over the years and most of these professionals do not know the risks they are exposed in order to perform their work activities. Considering that, this report has the objective of evaluating working conditions of hairdressers, manicure and chiropodist of small beauty saloons, identifying ergonomic, noise, biologic and chemical risks that these professional are exposed to. For ergonomic evaluation of activities, it was used RULA and OWAS tools, Corlett and Manenica diagram, and a questionnaire. The evaluation of workplace noise was made in three different beauty saloons in the city of Curitiba, by measuring with a dosimeter while drying hair activity. In order to evaluate biologic and chemical risks, a personal questionnaire was conducted for each professional where they should appoint which Personal Protective Equipments (PPEs) they usually wear to protect themselves from hazards. The results show that corrective measures should be applied in drying hair and chiropodist activities. These activities were pointed by the professionals evaluated as most stressful. About the workplace noise, it was observed that in only one beauty saloon the noise was over the limit established by NR-15 for 8 hours of exposition. In conclusion, first, beauty saloon professionals do not know the hazards which they are exposed in relation to not wearing or wearing incorrectly Personal Protective Equipments (PPEs), and second, the use of different methods to do the ergonomic evaluation allow us to achieve the most appropriate action level.